Distally based sural neuro-fasciocutaneous perforator flap for foot and ankle reconstruction: Surgical modifications for flap pedicle and donor site closure without skin graft. Issue 2 (February 2018) - Chi, Zhenglin; Chen, Yiheng; Chu, Tinggang; Gao, Weiyang; Li, Zhijie; Yan, Hede; Song, Yonghuan
Summary: Background: The conventional procedure of the sural neuro-fasciocutaneous flap enables the supply of blood and venous drainage by increasing the width of the adipofascial tissue and preserving tiny venous return routes. Moreover, skin graft is a common method for donor site closure, which may lead to some complications and influence the aesthetic appearance. We report modifications for a distally based sural neuro-fasciocutaneous perforator flap and a relaying flap for donor site closure without skin graft. Methods: Twelve patients undergoing the modified flap for foot and ankle reconstruction were included in this study between 2014 and 2016. A peroneal-based perforator, a superficial vein, and the vascular axis of the sural nerve were included in the pedicle. A Z-shape skin incision was performed to explore the perforator vessels and a relaying island perforator flap was used to close the donor site. Results: All flaps survived completely without necrosis. The area of the flaps ranged from 16 × 8 cm to 30 × 15 cm. The diameter width of the pedicle ranged from 1.0 to 2.0 cm. A relaying perforator island flap was used in 10 cases for donor site closure and no skin graft was performed. There were no serious donor site complications. All patients were satisfied with the aesthetic outcome postoperatively at the final follow-up. Conclusions: The distally based sural neuro-fasciocutaneous perforator flap is considered a reliable method for foot and ankle reconstruction. The modification for flap pedicle and donor site closure method without skin graft should be recommended.